317 The Standardized Ileal Digestibile Valine:Lysine Requirement in Lactating Sows. (10th April 2018) - Boessen, C; Graham, A; Greiner, L; Knopf, B; Touchette, K J; Goncalves, M A D; Orlando, U A D
Abstract: An experiment was conducted with 430 sows (PIC Camborough) to evaluate the ideal standardized ileal digestibile (SID) Val:Lys on sow and litter performance during a 23-d lactation period. The SID Val:Lys ratios measured were based on previously published literature and then values above and below reported values. Sows were randomly allotted within parity block (parity 1, parity 2, and parity 3+) to one of five corn soybean meal based lactation diets formulated to contain different levels of SID Val:Lys (0.50, 0.62, 0.75, 0.88, and 1.00, respectively). All diets were formulated to be isocaloric (3.3 ME Mcal/kg) with 0.95% SID Lys and contained vitamins and minerals that exceeded recommendations (NRC, 2012). Experimental diets were given to sows from 112 d of pregnancy throughout the 23-d lactation period. Litters were standardized within 48 h after farrowing. Sows were fed with the Howema computerized feeding system that mixed the high and low diets to create the intermediate diets, weighed the feed for each sow and then delivered the feed to each individual feeding hopper to record daily sow feed intake during lactation. Data were analyzed as a randomized complete block design using the PROC MIXED procedure of SAS with sow as the experimental unit and treatment as a fixed effect and parity as the random effect. Results were considered significant at P ≤ 0.05 and considered a trend at P > 0.05 and P ≤ 0.10. Sow ADFI was not significantly different (6.0, 6.0, 5.9, 5.6, 6.1 ± 0.18 kg/d, respectively). On average, sows consumed approximately 57g of SID Lys per day. Sow wean to estrus (5.2, 4.7, 5.3, 5.5, 4.5 ± 0.32 d, respectively) had a tendency to be significantly different as the Val:Lys ratio changed. Increasing the Val:Lys ratio resulted in no differences (2.66, 2.64, 2.76, 2.61, 2.62 ± 0.08 kg; P > 0.10) in average daily litter gain. There were no differences in sow weight loss or subsequent total born across the dietary treatments. Overall, increasing levels of SID Val:Lys may result in a difference in sow reproductive performance with no major influence in the other parameters.